Galois actions on non-abelian finite groups and applications - Lim, J (2017)
In this thesis, we consider the Galois actions on some finite characteristic quotients of the geometric fundamental groups of once-punctured elliptic curves. In particular, those of which can be naturally regarded as non-abelian lifts of usual mod ℓ Galois representations attached to elliptic curves. We also find its applications to some questions in the realm of Diophantine geometry.